Browsing evidence of the native and near-threatened Pudu puda deer in restoration plantings on Chiloe Island, Chile - Burger, Andreas; Bannister, Jan R.; Galindo, Nicole; Vargas-Gaete, Rodrigo; Vidal Ojeda, Osvaldo Javier; Schlegel, Bastienne (My University, 2019)
Few studies have focused on the actual extent and spatial patterns of browsing in relation to forest restoration, especially when browsing is done by deer with conservation status. Here, we present data from three forest restoration experiments located in priority forests for restoration in Chiloe Island in Chile. The aim of this study is to report evidence of browsing of the southern pudu (Pudu puda), a native and Near Threatened deer species. We visually assessed browsing for all individual seedlings and calculated the average browsing extent per plot and treatment. Since pudus as well as other deer species are known to preferably feed in open spaces, we hypothesized that Pilgerodendron uviferum planted seedlings will present higher browsing rates in places with lower shrub cover (bogs) and canopy cover (upland areas) (H1). In the case of degraded North-Patagonian forests we hypothesized that Nothofagus nitida planted seedlings will present higher browsing rates in places with higher %PPFD (Photosynthetic Photon Flux Density) and/or lower residual basal area (H2). Our results indicate that browsing ranged from 9.3% up to 84.0% depending on tree species and site condition. In burned forests, browsing was significantly higher (p < 0.01) when shrubs were removed (84.0% +/- 9.9) than by retaining them (68.9% +/- 11.6). In degraded old-growth forests, we found significantly higher browsing in places with higher degradation (p < 0.05). Furthermore, % PPFD was significantly correlated with browsing (rho: 0.535; p < 0.01). Based on our results, forest restoration efforts in Chiloe Island will face a great challenge in balancing the protection of Near Threatened wildlife and the restoration of tree species with conservation problems, especially in open/disturbed areas, where higher browsing was found.
Keywords: chile; forest management; forest restoration; herbivory; southern pudu